2016
DOI: 10.1177/0149206316668236
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cognitive Dissonance Theory in Management Research

Abstract: Since its introduction to the social psychology literature 60 years ago, Festinger’s cognitive dissonance theory (CDT) has been frequently applied to the management literature to explain and predict the motivational nature of dissonance in producing attitude and behavior change in managerial decision making and the broader organizational context. Yet many of the popular constructs that stem from CDT have since lost touch with more recent developments in the field of origin. In this paper, we provide a review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(150 citation statements)
references
References 72 publications
(116 reference statements)
5
128
0
4
Order By: Relevance
“…To the extent that organizations seek to hire individuals with these personality characteristics (through their direct assessment or indirectly by way of other selection criteria), we would expect employees to be better able to manage the cognitive and emotional impacts of identity coactivation. Even when SCC is high, coactivation experiences where two central identities are implicated may present challenges in the workplace, and organizational culture and managerial behavior may help to mitigate negative affect and facilitate the expression of multiple identities (Hinojosa, Gardner, Walker, Cogliser, & Gullifor, ; Hofhuis, van der Zee, & Otten, ).…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that organizations seek to hire individuals with these personality characteristics (through their direct assessment or indirectly by way of other selection criteria), we would expect employees to be better able to manage the cognitive and emotional impacts of identity coactivation. Even when SCC is high, coactivation experiences where two central identities are implicated may present challenges in the workplace, and organizational culture and managerial behavior may help to mitigate negative affect and facilitate the expression of multiple identities (Hinojosa, Gardner, Walker, Cogliser, & Gullifor, ; Hofhuis, van der Zee, & Otten, ).…”
Section: Discussionmentioning
confidence: 99%
“…16 Studies have shown that they will do so by altering the cognition that is the least resistant to changes. 17 This may, for instance, require individuals to modify their behavior or attitude, to alter one of the conflicting cognitions, or to introduce a new element in their belief system. 18 Failure to reduce dissonance will conversely sustain the negative cognitive state.…”
Section: Research Approach and Theoretical Frameworkmentioning
confidence: 99%
“…Regarding cognitive dissonance, most studies have been conducted in the field of social psychology and management research [44]. Cognitive dissonance theory has been widely used to explain organisational behaviour, such as job demands and job satisfaction [45], staffing risks and safe staffing [46] and also consumer behaviour [47].…”
Section: Predictors Of Training Attitudesmentioning
confidence: 99%